The Effect of Effleurage Massage on Lowback Pain In Trimester Iii Pregnant Women At Mandala Puskesmas, Lebak Regency In 2021 - Nani Yuningsih; Kadar Kuswandi; Siti Rusyant (Institute of Computer Science (IOCS), 2022)
The biopsychosocial needs of pregnant women have not been explored. We need an intervention that is able to restore the balance of the body. The purpose of this study was to prove the effect of effleurage massage on back pain in the third trimester pregnant women. A quasi-experimental study with randomized control group pre-test post-test design. The division of the intervention group was 18 people with effleurage massage and the control group was 16 people with pregnant exercise. Observations using the ODI scale for 3 weeks at the end of week 4 were evaluated. Before and after treatment, each group did not have a difference in the average pain score (intervention group p=0. 2 and control group p=0.830). The difference between the FHR differences between groups was not significant, the p value = 0.31. The intervention with effleurage massage was proven to reduce back pain discomfort in third trimester pregnant women compared to the exercise group, using the ODI scale. There is a need for continuous care in health services for mothers such as complementary services for effleurage massage as an alternative to care for pregnant women at health centers.